Asynchronous evolution of interdependent nest characters across the avian phylogeny - Fang, Yi-Ting; Tuanmu, Mao-Ning; Hung, Chih-Ming (Nature communications, 2018)
Nest building is a widespread behavior among birds that reflects their adaptation to the environment and evolutionary history. However, it remains unclear how nests evolve and how their evolution relates to the bird phylogeny. Here, by examining the evolution of three nest characters—structure, site, and attachment—across all bird families, we reveal that nest characters did not change synchronically across the avian phylogeny but had disparate evolutionary trajectories. Nest structure shows stronger phylogenetic signal than nest site, while nest attachment has little variation. Nevertheless, the three characters evolved interdependently. For example, the ability of birds to explore new nest sites might depend on the emergence of novel nest structure and/or attachment. Our results also reveal labile nest characters in passerines compared with other birds. This study provides important insights into avian nest evolution and suggests potential associations between nest diversification and the adaptive radiations that generated modern bird lineages. Nearly all bird species build nests; however, there is extensive variation in both how and where their nests are built. Here, Fang and colleagues reconstruct the evolution of nest structure, nest site and nest attachment across all extant bird families.